ACTION MECHANISMS OF ANTIBIOTICS VS NATURAL INGREDIENTS AGAINST MICROBES - Maneika Dulanjali Kamathewatta, (International Journal of Ayurveda and Pharma Research, 2020)
Antimicrobial resistance is being identified as one of the major threats in the health sector and to humans. The main reason of development of the resistance is established as acceleration of the natural evolution of the bacteria due to unnecessary constraints provided by the antimicrobial agents. After exploiting and exhausting the available antibiotics, development of new antibiotics is proven to be an expensive and difficult task and therefore alternative solutions such as use of nanoparticles, bacteriophage, natural ingredients, and new mechanisms such as quorum sensing ability were staged. It is important to identify the mechanism by which each of these new ingredients act in bacteria and reaction in the host environment to avoid similar misuses and creation of resistance. This review focuses on summarizing action mechanisms of antibiotics and resistance mechanisms of microbes and gathering probable action and resistance mechanisms of herbal ingredients. Antibiotic action is mainly obtained by inhibiting a bacterial structure or specific metabolic activity that is necessary for survival of bacteria. Some plants in contrast do not focus on inhibiting bacteria but minimizing the effects on host by nullifying the toxins and improving the immunity. Some other plants can disrupt the communication between bacteria and biofilm formation. One of the most important ability of some herbal ingredients is to overpass the resistance and they are called inhibitors. With the inhibitors there are new possibilities of reintroducing antibiotics. Plants with bactericidal capacity must use carefully to avoid creating resistance and should conduct further research for calculating proper dosages.